Internet Use in the Context of Senior School Children' Social Expertise - kaur, Ms. Amritpal (The journal of contemporary issues in business and government, 2019)
In the twenty-first century, internet usage is pervasive in all aspects of life. The internet's accomplishments in the realm of education are equally noteworthy. Although the internet is preferred for education, excessive non- essential internet use is a source of concern for kids, parents, schools, and communities. Excessive non-essential internet use has been linked by several researchers to a variety of psychiatric illnesses, negative health impacts, declining scholastic attainment, and decreased social skills. A person must have social skills or competences that will enable him to be a better adjusted member of society. This will assist him in maintaining mental health, tranquilly, and success in his life. The purpose of this work is to investigate secondary school students' Internet usage in connection to their social competency. The study's sample consists of 1000 randomly selected secondary school students from Jalandhar's rural and urban districts in equal proportion. The researchers used two self-created and standardised scales to collect data: the Internet Usage Scale by Saini S. and Kaur P. (2017) and the Social Competence Scale by Sharma and Shukla (1992) Males use the internet much more than females, and urban students use the internet significantly more than rural pupils, according to the findings. Furthermore, the data show that there is a substantial difference in social competency scores between secondary school pupils who use the internet in low, high, and moderate amounts. However, the social competency ratings of students from different subgroups generated by the interaction effect of Internet usage levels, gender, and location show no significant differences. In terms of the association between internet usage and social competency, the two variables were shown to have a strong negative relationship.